More than just water - Planning scenarios for a sustainable development of the Belgian part of the North Sea - Peter Vanden Abeele (European Regional Science Association (ERSA), 2005)
Although the sea is one of the most decisive factors for the planning of any coastal region, Belgian planners and policymakers have been doing it with their back towards the sea. But in the face of new spatial claims for more marine transport, windmill farms, sand and gravel extraction, and even nature conservation, policymakers are forced to rethink the role of this seemingly endless surface of water. In the future this role will become even more important as the sea level will rise due to climate change. The dominant land-oriented planning discourse of which the Belgian 'Atlantic Wall' and the Dutch 'Delta works' are exemplary, will no longer be tenable within the concept of sustainable spatial development. For more than a decade, different departments of the Ghent University have engaged in research on the BCP, the Belgian Continental Part of the North Sea. Through the years valuable information about the use, the natural and economical dynamics and even the socio-cultural meaning of this small part of the North Sea has been gathered. But only recently with the introduction of spatial planners in the GAUFRE-research project "towards a spatial plan for the Belgian part of the North Sea” (financed by the Belgian Federal Public Planning Service Science Policy), the main focus shifted from gathering scientific information, as part of an extensive analysis of the BCP, to formulating future scenarios by which we could plan the BCP. This paper, as a result of the GAUFRE-project, formulates new planning approaches for the development of the BCP and the 67 km short strip of the Belgian coast, based on the specific dynamics and characteristics of the sea itself. In order not to end in a final regional plan or a fixed set of planning regulations but in a totally new and sea-oriented planning discourse, the research tries to open the perspective on the sea and the coast by using different development scenarios. Starting from three core values – these are the social, economical and ecological value of the BCP - or a combination of two of them, six thematic scenarios were developed through design-oriented research. In every scenario the underused potential of the water was looked at in a totally different way in order to develop the water in a sustainable way. Water proved to be a much richer resource by which we could plan the sea and the coast than it is currently considered to be. Whether it is used for transport (short sea shipping, harbour islands), recreation (at the coast or on new islands), fishery (in concession areas or based on a rotation system), nature conservation (dynamic coastline, natural coastal defence, Marine Protected Areas) or even for new functions like windmill farms, aquaculture and mariculture (as land-based development of resources of the sea), water becomes a real structuring element.
Keywords: 330